The cost of integrating external technologies: Supply and demand drivers of value creation in the markets for technology - Ceccagnoli, Marco; Jiang, Lin (Strategic Management Journal, 2013)
Abstract A classic question faced by technology suppliers and buyers is whether to compete in the product markets or to cooperate through licensing. We address this question by examining an important, demand‐side barrier to licensing—the buyers' cost of integrating a licensed technology. We argue that this cost can be affected by suppliers' knowledge transfer capabilities, buyers' absorptive capacity, and the cospecialization between R&D and downstream activities in the buyers' industries. Following this argument and a stylized bargaining model, we hypothesize that the supplier's knowledge transfer capability stimulates licensing. Moreover, the importance of this capability increases when licensing to industries where potential buyers have weak absorptive capacity or R&D and downstream activities are cospecialized. We find support for our hypotheses using a panel dataset of small ‘serial innovators.’ Copyright © 2012 John Wiley & Sons, Ltd.